William of Malmesbury on pagan Slavic oracles - Słupecki, Leszek Paweł (Studia mythologica Slavica, 1999)
The article brings to the attention of the scholarly world a hardly known medieval source Gesta Regum Anglorum written by William of Malmesbury. Who was an early 12th century English benedictine monk from Malmesbury in Western England. The article revolves around the outmost relevance of William of Malmesbury to the study of pre-Christian Slavic religion, and provides two interpretations of William's account.
Keywords: William of Malmesbury, ok. 1090-1143; mitologija; mythology; slovanska mitologija; poganstvo; Slavs; Slovani; prerokbe; primary source; zgodovinski viri